Identification and functional analysis of immune deficiency (IMD) from Scylla paramamosain: The first evidence of IMD signaling pathway involved in immune defense against bacterial infection in crab species. Issue 81 (October 2018) - Zhou, Yi-Lian; Wang, Lan-Zhi; Gu, Wen-Bin; Wang, Cong; Zhu, Qi-Hui; Liu, Ze-Peng; Chen, Yu-Yin; Shu, Miao-An
Abstract: Immune deficiency (IMD) pathway, one of the most essential pattern recognition receptor signaling pathways, plays vital roles in innate immune responses to eliminate pathogen infection in invertebrates. In the present study, an immune deficiency ( IMD ) gene and two NF-κB family members, Relish and Dorsal, were identified and characterized in mud crab Scylla paramamosain for the first time. The deduced Sp IMD, Sp Relish and Sp Dorsal protein contained conserved death domain and classical NF-κB domains, respectively. Phylogenetic analysis suggested that Sp IMD was classified into the invertebrate IMD branch, and Sp Relish could be classified into the type I NF-κB class while Sp Dorsal could be grouped into the type II NF-κB class. Tissue distribution results showed these three genes were ubiquitously expressed in all tested tissues. The expression patterns of IMD signaling pathway and NF-κB genes, including SpIMD, SpIKKβ, SpIKKε, SpRelish and SpDorsal, were distinct when crabs were stimulated with Vibro alginolyticus, indicating that they might be involved in responding to bacterial infection. When SpIMD was silenced by in vivo RNA interference assay, the expression levels of IMD pathway and antimicrobial peptides (AMPs) genes, including SpIKKβ, SpRelish, SpALF1-6 and SpCrustin, were significantly down-regulated ( p  < 0.05). Correspondingly, the bacteria clearance ability of hemolymph was extremely impaired in IMD silenced crabs. Overall, the IMD played vital roles in innate immune response by regulating the expressions of its down-stream signaling genes and AMPs in S. paramamosain . These findings might pave the way for a better understanding of innate immune system and establish a fundamental network for the IMD signaling pathway in crustaceans. Highlights: The SpIMD, SpRelish and SpDorsal genes were firstly identified and characterized. IMD signaling pathway existed in crab and responded to bacterial infection. IMD regulated expressions of antimicrobial peptides genes in S. paramamosain.